Aerva lanata extract restores cellular viability and mitochondrial function against gentamicin induced nephrotoxicity on human embryonic kidney cells - Manju, L; Ambili , S; Rejiya , CS; Vishnu, SL; Radhika , A; Rajesh, R (Plant Science Today, 2025)
Aerva lanata, commonly used in traditional medicine systems such as Ayurveda and Siddha, is well known for its diuretic and lithotriptic properties in the management of urolithiasis and other urinary tract disorders. However, despite its widespread traditional use, comprehensive studies elucidating the nephroprotective mechanisms of A. lanata under conditions of chemically induced renal damage remain limited, warranting further investigation. The current study investigated the nephroprotective properties of ethyl acetate extract of Aerva lanata (EA-AL) against gentamicin induced nephrotoxicity in human embryonic kidney (HEK293) cells. The initial phytochemical evaluation of EA-AL indicated the presence of tannins, which were later quantified. The antioxidant activity of EA-AL was evaluated using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay, while its nephroprotective activity was evaluated using the 2,3-Bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) assay. The results demonstrated that EA-AL significantly restored cell viability in gentamicin-exposed cells. Gentamicin exposure induced oxidative stress, evidenced by increased lipid peroxidation products and diminished antioxidant enzyme levels. The levels of antioxidant enzymes were effectively elevated and membrane peroxidation was diminished through co-treatment with EA-AL. Moreover, 2', 7’-Dichlorofluorescin diacetate (DCFDA) staining demonstrated that gentamicin exposure led to increased Reactive Oxygen Species ROS production, which was significantly reduced by EA-AL treatment. Exposure to gentamicin led to an elevation in depolarized viable and non-viable cells, indicating a disruption in mitochondrial membrane potential and overall mitochondrial integrity. The co-treatment with EA-AL successfully restored the population of viable cells. The reinstatement of cellular viability and mitochondrial function highlights the nephroprotective potential of EA-AL against imposed toxicity in HEK293cells.